A survey among Brazilian thoracic surgeons about the use of preoperative 2D and 3D images - Cipriano, Federico Enrique Garcia; Arcêncio, Livia; Dessotte, Lycio Umeda; Rodrigues, Alfredo José; Andrade Vicente, Walter Villela de; Barbosa Évora, Paulo Roberto (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Background: Describe the characteristics of how the thoracic surgeon uses the 2D/3D medical imaging to perform surgical planning, clinical practice and teaching in thoracic surgery and check the initial choice and the final choice of the Brazilian Thoracic surgeon as the 2D and 3D models pictures before and after acquiring theoretical knowledge on the generation, manipulation and interactive 3D views. Methods: A descriptive research type Survey cross to data provided by the Brazilian Thoracic Surgeons (members of the Brazilian Society of Thoracic Surgery) who responded to the online questionnaire via the internet on their computers or personal devices. Results: Of the 395 invitations visualized distributed by email, 107 surgeons completed the survey. There was no statically difference when comparing the 2D vs. 3D models pictures for the following purposes: diagnosis, assessment of the extent of disease, preoperative surgical planning, and communication among physicians, resident training, and undergraduate medical education. Regarding the type of tomographic image display routinely used in clinical practice (2D or 3D or 2D–3D model image) and the one preferred by the surgeon at the end of the questionnaire. Answers surgeons for exclusive use of 2D images: initial choice =50.47% and preferably end =14.02%. Responses surgeons to use 3D models in combination with 2D images: initial choice =48.60% and preferably end =85.05%. There was a significant change in the final selection of 3D models used together with the 2D images (P